The simple preparation of robust mesoporous N/C co-doped Cu7.2S4 for effectively removal of oxytetracycline based on activating peroxymonosulfate - Liu, Xun; Pei, Yan; Cao, Mengbo; Yang, Hongbing; Li, Yongsheng (Journal of environmental chemical engineering, 2022)
In this work, the robust mesoporous N/C co-doped Cu7.2S4 (N/C-Cu7.2S4) and CuS were synthesized by simple one-step hydrothermal method for degradation of oxytetracycline (OTC). Based on the XRD, SEM, TEM, EDX as well as BET analysis, robust phase structure and dispersed active sites favorable to degradation process was proved. Systematically exploring the effect of experiment index (i.e., the dosage of peroxymonosulfate and catalyst, temperature, pH, etc.) on the degradation performance to obtain the optimal operating conditions. Degradation efficiency of 99.9 % could be achieved within 30 min, under suitable conditions. Moreover, HCO3- played a promoting role in the early stage of degradation mainly due to the CO3•- which was beneficial to the selective removal of OTC. The degradation efficiency of the material could still reach 94.8 % after three cycles. The •OH radical and 1O2 played a major role in degradation process, which was proved by radical quenching experiments and electron paramagnetic resonance (EPR). The possible degradation pathways of OTC were investigated on the basis of liquid chromatography-mass spectrometry (LC-MS). Different actual water sample tests confirmed its applicability in various filed, in which the degradation efficiency of OTC still could reach up 74.6 % in hospital wastewater. The experimental results showed that the N/C-Cu7.2S4 has outstanding performance, good stability and cyclability for the effective degradation of OTC. [Display omitted] •Preparation of N/C co-doped Cu7.2S4 by one-step hydrothermal method.•N/C co-doped Cu7.2S4 have excellent ability to degrade oxytetracycline (99.9 %).••OH and 1O2 dominate the degradation process, while SO4•- plays a lower role.•HCO3- effectively promoted the oxytetracycline degradation rate by oxidation.